Investigating the Hyers–Ulam Stability of the Generalized Drygas Functional Equation: New Results and Methods - Gang Lyu; Yang Liu; Yuanfeng Jin; Yingxiu Jiang (Axioms)
In this paper, we explore the Hyers–Ulam stability of a generalized Drygas functional equation, which extends the classical Drygas equation by incorporating additional parameters and conditions. Our investigation focuses on mappings from a real vector space into a Banach space and employs the fixed-point method to establish stability criteria. Our findings provide new insights into the conditions under which the generalized Drygas equation maintains stability, contributing to the broader understanding of functional equations in mathematical analysis. The results have implications for the study of functional equations and their applications in various mathematical contexts.